Skill and Entrepreneurship Development in Post-harvest Technology and Value Addition through Agribusiness Incubation - Singh, Ranjeet; Sharma, Alka; Singh, R K (Indian Farming, 2020)
India is endowed with varied agroclimate, which facilitates production of temperate, sub-tropical and tropical agricultural commodities which lead to main generator of employment and income to millions of people. Entrepreneurship in postharvest technology and value addition is not only an opportunity but also a necessity for improving the production and profitability. These incubators can take the form of comprehensive occupational schools, offering rural producers and workers sufficient knowledge, experience, infrastructure, and means to become agribusiness entrepreneurs. This endogenous movement can have farreaching effects, promoting the overall modernization of primary production, industrialization, and marketing and development of rural areas. The ABI CIPHET Ludhiana take care of technologies, advise/ guide the farmers and entrepreneurs and young unemployed youth for exploring new business opportunities and therefore help to enhance and improve economic development through post-harvest processing and value addition of agriculture produce.